Determinan Shopping Opinion: Perspektif Klien Dan Kantor Akuntan Publik - Alfina Dhia Ulfa; Sulhani Sulhani (JAS (Jurnal Akuntansi Syariah), 2021)
This study analyzes the effect of audit market competition, client size, and financial distress on shopping opinions. The sample used in this study is a manufacturing company listed on the Indonesia Stock Exchange for 2016 to 2017. The data used in the study were 76 data from the company's annual reports. The data analysis method used was binary logistic regression. This study indicates that audit market competition and client size do not affect shopping opinion practices. However, financial distress has a significant positive effect on the tendency to practice shopping opinion. This indicates that a company with an excellent financial condition chooses to change its auditor compared to the same auditor; this is done because financially, the company can change public accounting.